Using data to improve the health of coastal communities: The Coda Network - Patel, Martyn; Ford, Elizabeth; Murray , Emily; Ward , Phil (International Journal of Population Data Science, 2026)
Background Since 2021, the discrepancy in healthy life expectancies between coastal and in-land towns in the United Kingdom has been highlighted, with several recommendations around using health data to identify and address potential health improvements. We describe both the processes and the lessons learned in building a new regional network with a critical mass of stakeholders to tackle a well-recognised infrastructural health problem, in a relatively under-resourced area. Methods In 2022 the Coastal Data Network (Coda) was formed as part of the Eastern Academic Research Collaboration in the Eastern and Southeastern coastal regions of England, UK. A range of stakeholders from local authorities, national health service and universities have come together to share best practice and expertise to tackle coastal health inequalities using routinely collected health and administrative data. We have hosted a series of workshops and a conference as well as online meetings. Results Two case studies are presented showing how Coda has responded to system needs or shared best practice in response to emergency situations. We are currently working to sustain the network beyond its initiation phase and to seek external funding for collaborative research activity in the region. Conclusion The Coda Network has been established to enhance capacity for understanding and improving the health and lives of coastal populations. Key to retention and growth of the membership has been an early and vigorous commitment to sharing "best practice" examples. This network approach enlarges the pool of data available to Coda members allowing us to plan future population data science projects.